(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Simulation-based education is not sufficiently implemented in many higher educational institutions. In the process of creating a tool for the formation and final assessment of specific competencies, we mainly rely on this pedagogical technology to support the development of psychiatry as a science. The study presented in this article focuses on examining the learning process and the impact of simulation in psychiatry, as well as the support it provides to medical institute students in mastering the subject.